2017
DOI: 10.1002/dev.21540
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cortisol slope at 6 months predicts infant cortisol slope and EEG power at 12 months

Abstract: Physiological stress systems and the brain rapidly develop through infancy. While the roles of caregiving and environmental factors have been studied, implications of maternal physiological stress are unclear. We assessed maternal and infant diurnal cortisol when infants were 6 and 12 months. We measured 12-month infant electroencephalography (EEG) 6–9 Hz power during a social interaction. Steeper 6-month maternal slope predicted steeper 12-month infant slope controlling for 6-month infant slope and breastfeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 91 publications
(144 reference statements)
1
24
0
Order By: Relevance
“…Some primiparas have insufficient knowledge of breastfeeding, so they reject breastfeeding and fail to continue breastfeeding. Therefore, changing the feeding intention of primiparas and urging them to continue breastfeeding are important measures to encourage breastfeeding (13,14). The TPB was first proposed by US psychologist Ajzen in 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Some primiparas have insufficient knowledge of breastfeeding, so they reject breastfeeding and fail to continue breastfeeding. Therefore, changing the feeding intention of primiparas and urging them to continue breastfeeding are important measures to encourage breastfeeding (13,14). The TPB was first proposed by US psychologist Ajzen in 1985.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneity in early life environments that create stress, in concert with the reliance on parental perception of stress, makes it difficult to develop a mechanistic understanding of chronic stress. In addition to parental report, there is increased interest in the assessment and characterization of physiological stress as linked to early neural development, given that physiological stress has been related to brain function and development (McEwen, 2004; St. John, Kao, Liederman, Grieve, & Tarullo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Johnet al, 2017). To our knowledge, only one study has examined how maternal stress physiology may alter task-related infant brain functioning (St. John et al, 2017). This study found that maternal point-in-time salivary cortisol (collected at infant age 6 months) predicted later infant brain function (6-9 Hz power).…”
mentioning
confidence: 99%
“…Some populations, such as children and adults with cognitive disorders, are limited in attending laboratory EEG sessions, which can be lengthy and uncomfortable. Therefore, efforts that are aimed at transferring laboratory methodologies to different everyday contexts create the possibility for their inclusion in studies with greater ecological value [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%